Sustainable Competitive Advantage of Riau Malay Weaving Industry Based on Local Wisdom - Annisa Mardatillah; Rosmayani Rosmayani; Shafira Amalia Ramadhani (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2020)
This study aims to analyze the strategy of developing Riau Malay woven fabrics’ competitiveness and what factors predominantly influence efforts to develop the sustainable competitive advantage of the Riau malay weaving industry based on local wisdom of Malay fabrics in Pekanbaru. The sampling technique chosen was using a purposive sampling of 14 SMEs of Riau Malay woven fabric in Pekanbaru. SWOT analysis was applied as an analysis tool. This research is more in looking at the Riau Malay woven fabric craftsmen based on their ethnic abilities to differ from previous research. The research findings show aspects of product strength consisting of authenticity values of motifs/patterns based on typical regional philosophies not possessed by other regions as a cultural identity. Human resources’ knowledge and skills in producing Riau Malay Weaving fabrics inimitable, and there is no substitute for being a force that will not quickly transfer to other companiesKeywords: woven fabric industry, small industry, local wisdom, sustainable competitive advantage* Departement of Business Administration, Universitas Islam Riau, Jl. Kaharudin Nasution KM 113, Simpang Tiga, Bukit Raya, Pekanbaru, Indonesi https://doi.org/10.21632/irjbs.13.3.227-240